1989
DOI: 10.1111/j.1749-6632.1989.tb53242.x
|View full text |Cite
|
Sign up to set email alerts
|

Microdialysis Studies of Brain Norepinephrine, Serotonin, and Dopamine Release During Ingestive Behavior Theoretical and Clinical Implicationsa

Abstract: This minireview deals with the possible roles of monoamines in feeding and feeding disorders. The introduction sketches the results of earlier studies with local drug injections and selective neurotoxins which provided pharmacological evidence that monoamines can influence food intake and body weight. A table summarizing this evidence is used to list monoamine changes that could underlie anorexia or hyperphagia. It is apparent that abnormalities in the monoamines, along with their cotransmitters, could cause m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(107 citation statements)
references
References 57 publications
6
100
1
Order By: Relevance
“…There is high comorbidity between BN and substance abuse, and there is a considerable body of data suggesting that disturbed appetitive behaviors for food in BN may reflect a dysregulation of reward mechanisms that is common to both BN and substance-abuse disorders [317]. Indeed, early hallmark preclinical studies by Hoebel and colleagues [318] highlighted commonalities between BN and addiction disorders in terms of neurobiology, psychopharmacology, neurochemistry, and behavior [319]. Binge eating has also been suggested to serve an emotion regulatory function, and thus has many qualities of reward-mediated behaviors [320].…”
Section: Reviewmentioning
confidence: 99%
“…There is high comorbidity between BN and substance abuse, and there is a considerable body of data suggesting that disturbed appetitive behaviors for food in BN may reflect a dysregulation of reward mechanisms that is common to both BN and substance-abuse disorders [317]. Indeed, early hallmark preclinical studies by Hoebel and colleagues [318] highlighted commonalities between BN and addiction disorders in terms of neurobiology, psychopharmacology, neurochemistry, and behavior [319]. Binge eating has also been suggested to serve an emotion regulatory function, and thus has many qualities of reward-mediated behaviors [320].…”
Section: Reviewmentioning
confidence: 99%
“…Early microdialysis studies found that instrumental feeding responses or appetitive hypothalamic stimulation releases DA in the NAc, and it can stay high for some time afterward [16]. DA release can carry information as to sucrose concentration and thus palatability [17].…”
Section: Feeding and Satietymentioning
confidence: 99%
“…It is possible that conditioned increases in dopaminergic activity that are elicited by stimuli associated with eating play a role in craving for food (Berridge, 1996). Initially, dopamine is released when food is consumed (Hoebel, Hernandez, Schwartz, Mark, & Hunter, 1989), and its activity in the nucleus accumbens may relate not only to consumption but also to rewarding properties of food (Hernandez & Hoebel, 1988). Over repeated pairings of an environmental stimulus with eating, dopamine is released after presentation of a cue paired with food in anticipation of eating.…”
Section: Dopamine and The Neurobiology Of Food Reinforcementmentioning
confidence: 99%